Tesla Inc Supply Chain Management Analysis and The Role of ERP In It - cuandra, Fendy; Irvin, Irvin; Joven, Alfred; Oktarianto, Eddy; Viviani, Viviani; Jovianto, Jovianto; Yolanda, Yolanda; Charmaine, Charmaine (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
Tesla Inc. is a company operating in the automotive industry and was founded from the United States of America. In the company’s business operations, Tesla Inc. needs a supply chain management strategy for a streamlined business process. This article will be discussing about Tesla Inc.’s supply chain management and the role of ERP in it. Tesla Inc. implements vertical supply chain integration strategy for the company’s supply chain management. Also in the business process of the company, Tesla Inc. implements ERP system known as WARP which is developed internally by the company itself to integrate business functions.